2-Arylquinazolin-4(3H)-ones: A new class of α-glucosidase inhibitors. Issue 23 (1st December 2015) - Javaid, Kulsoom; Saad, Syed Muhammad; Rasheed, Saima; Moin, Syed Tarique; Syed, Naima; Fatima, Itrat; Salar, Uzma; Khan, Khalid Mohammed; Perveen, Shahnaz; Choudhary, M. Iqbal
Graphical abstract: Abstract: Twenty-five derivatives of 2-arylquinazolin-4(3 H )-ones (1 –25 ) were evaluated for their yeast (Saccharomyces cerevisiae) α-glucosidase inhibitory activities. All synthetic compounds, except1 and6, were found to be several hundred fold more active (IC50 values in the range of 0.3 ± 0.01–117.9 ± 1.76 μM), than the standard drug, acarbose (IC50  = 840 ± 1.73 μM). The enzyme kinetic studies on the most active compounds12, 4, 19, and13 were performed for the determination of their modes of inhibition and dissociation constants K i . Study of the modes of inhibition of compounds12, and4 were also performed using molecular modeling techniques. In brief, current study identifies a novel class of α-glucosidase inhibitors which can be further studied for the treatment of hyperglycemia and obesity.